2014
DOI: 10.1371/journal.pone.0098277
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characterization of Vestibular Efferent Brainstem Neurons Using a Transgenic Mouse Model

Abstract: The functional role of efferent innervation of the vestibular end-organs in the inner ear remains elusive. This study provides the first physiological characterization of the cholinergic vestibular efferent (VE) neurons in the brainstem by utilizing a transgenic mouse model, expressing eGFP under a choline-acetyltransferase (ChAT)-locus spanning promoter in combination with targeted patch clamp recordings. The intrinsic electrical properties of the eGFP-positive VE neurons were compared to the properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 69 publications
8
29
0
Order By: Relevance
“…However, the mammalian EVS can possess multiple groups, dependent on species. Mouse and cat have only one cluster of EVN neurons, located near the facial nerve genu (Warr, 1975 ; Leijon and Magnusson, 2014 ; Mathews et al, 2015 ). In other mammalian studies, more than one cluster was observed with the major nucleus being referred to as group e (Goldberg and Fernàndez, 1980 ), located dorsal and/or ventral to the facial nerve (Shumilina et al, 1986 ; Perachio and Kevetter, 1989 ).…”
Section: Anatomy and Morphology Of The Evs Across Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mammalian EVS can possess multiple groups, dependent on species. Mouse and cat have only one cluster of EVN neurons, located near the facial nerve genu (Warr, 1975 ; Leijon and Magnusson, 2014 ; Mathews et al, 2015 ). In other mammalian studies, more than one cluster was observed with the major nucleus being referred to as group e (Goldberg and Fernàndez, 1980 ), located dorsal and/or ventral to the facial nerve (Shumilina et al, 1986 ; Perachio and Kevetter, 1989 ).…”
Section: Anatomy and Morphology Of The Evs Across Vertebratesmentioning
confidence: 99%
“…More recent work has investigated the physiological characteristics of EVN neurons including passive membrane properties, discharge profiles, and synaptic input profile. Cholinergic EVN neurons were identified in one study using transgenic mice engineered to express enhanced green fluorescent protein (eGFP) under the choline-acetyltransferase (ChAT) promotor (Leijon and Magnusson, 2014 ). In another study, the location of EVN neuronal recordings were confirmed using retrograde tracing from the posterior semicircular canal in ChAT:: tdTomato transgenic mice which confirmed the location of cholinergic EVN neurons, and the staining of each recorded neuron (Mathews et al, 2015 ).…”
Section: Physiology Of Evn Neuronsmentioning
confidence: 99%
“…A1, arrow, A2) and VNTB (Fig. B1,B2) neurons (Leijon and Magnusson, ). Note that the ChAT‐positive neurons of the abducens nucleus do not express Brn3b (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that cochlear efferents have to be stimulated at least at 10 Hz to facilitate their normally low probability of release (Ballestero et al, 2011), and it is a reasonable assumption that the same is required for vestibular efferents. Vestibular efferents in mouse brainstem slices (Leijon and Magnusson, 2014;Mathews et al, 2015Mathews et al, , 2017 have spontaneous resting discharges of up to 5 spikes/s. The main input to efferent neurons is provided by the vestibular nuclei, and the spontaneous activity of vestibular nuclei neurons is ϳ5 times higher in alert mice (57.5 Ϯ 4.2 spike/s) (Beraneck and Cullen, 2007) compared Figure 8.…”
Section: Discussionmentioning
confidence: 99%